A Scoping Review of Neuromuscular Electrical Stimulation to Improve Gait in Cerebral Palsy: The Arc of Progress and Future Strategies - Mooney, Jake A.; Rose, Jessica (Frontiers in Neurology, 2019)
Background: Neuromuscular deficits of children with spastic cerebral palsy (CP) limits mobility, due to muscle weakness, short muscle-tendon unit, spasticity, and impaired selective motor control. Surgical and pharmaceutical strategies have been partially effective but often cause further weakness. Neuromuscular electrical stimulation (NMES) is an evolving technology that can improve neuromuscular physiology, strength and mobility. This review aims to identify gaps in knowledge to motivate future NMES research. Methods: Research publications from 1990-July 20th 2019 that investigated gait-specific NMES in CP were reviewed using the PubMed and Google Scholar databases. Results were filtered by the National Institute of Neurological Disorder and Stroke common data elements guidelines for CP. The Oxford Centre for Evidence Based Medicine guidelines were used to determine levels of evidence for each outcome. Gait-specific NMES research protocols are described, with implications for future research. Results: Eighteen studies met inclusion criteria, reporting on 212 participants, 162 of whom received NMES while walking, average age of 9.8 years, GMFCS levels I–III. Studies included 4 randomized control trials, 9 cohort studies and 5 case studies. A historical trend emerged that began with experimental multi-channel NMES device development, followed by the commercial development of single-channel devices with inertial sensor-based gait event detection to facilitate ankle dorsiflexion in swing phase. This research reported strong evidence demonstrating improved ankle dorsiflexion kinematics in swing and at initial contact. Improved walking speed, step length, and muscle volume were also reported. Improvements in global walking scores were not consistently found, motivating a return to investigating multi-channel NMES applications. Conclusions: Research on single-channel gait-specific NMES found that it improved ankle motion in swing but was insufficient to address more complex gait abnormalities common in CP, such as flexed-knee and stiff-knee gait. Early evidence indicates that multi-channel gait-specific NMES may improve gait patterns in CP, however significantly more research is needed. The conclusions of this review are highly limited by the low level of evidence of the studies included. This review provides a historical record of past work and a technical context, with implications for future research on gait-specific NMES to improve walking patterns and mobility in CP.